Regulatory Issues and Challenges on A2P SMS Communication in Malaysia - Asma Md. Isa, Wan Amizah Wan Mahmud, Arina Anis Azlan, Anita Morah Abas, Wan Idros Wan Sulaiman, Muhammad Adnan Pitchan, Umi Hamidaton Mohd Soffian Lee, Radin Anis Adlina Radin Hasbani (International Journal of Advanced Science and Technology, 2020)
The article studies the regulatory issues and challenges raised by Content Aggregator Providers in Malaysia. Application-to-Person (A2P) has an important role to play in the mobile ecosystem through strengthening and deepening the process of competition and any-to-any connectivity subsequently to address the issues and challenges faced by the access seeker in the regulatory landscape. The main objective of regulation is to ensure a competitive market and provide the necessary protections for consumers. Communications and multimedia industry market should be determined primarily by market forces. Regulator intervention may be justified and clear demarcation between regulation to protect against market failure and regulation to ensure long term benefits to the end users. Finally, recommendations have been put forward at the end of this paper for the reference of future research. Keywords: A2P SMS communication, access regulation.